Context of women in agriculture in Baja California Sur - Coronado-García, Manuel Arturo; Mayoral-García, Manuel Benjamín; Isaac Shamir; Leyva-Carreras, Alma Brenda; Rossetti-López, Sergio Ramón (Revista Mexicana de Ciencias Agrícolas, 2023)
This research allowed us to know the factors that affect the productivity of women in agriculture, as well as to explore the existing working conditions that could also impact the role of women in their productive environment. The study was conducted in 2019. The objective of this work was to identify the main problems experienced by women with respect to men in the sustenance of households and performance in agricultural activities. To this end, a descriptive study of mixed approach was carried out, which was applied in two agricultural regions of BCS, collecting information through a survey. The results show differences in relation to income, working hours, management of household expenses and time spent on domestic work. The work concludes that there is no equality, so it is important to promote the value of people of both sexes in the social dynamics of the communities analyzed.